Take it of your shoulders: Providing scaffolds leads to better performance on mathematical word problems in secondary school children with developmental coordination disorder. (October 2020) - Reynvoet, Bert; Marinova, Mila; Sasanguie, Delphine
Highlights: Word problem solving was examined in 14−16 year old DCD children. Scaffolds cueing the intermediate steps of the solution process led to better performance. DCD children performed as accurate as controls on fact retrieval and procedural calculation. DCD children demonstrated differences on executive functioning when compared to controls. Abstract: Background: Many children with developmental coordination disorder (DCD) have mathematical problems which are more pronounced for mathematical skills that also require executive functions. Although empirical evidence is missing, math and special education need teachers of children with DCD report difficulties with mathematical word problem solving that can be remediated by providing the children with scaffolds cueing the intermediate steps. Aims: This study aims to find empirical evidence for the effectivity of such additional support. In addition, we want to investigate whether the difficulties are due to inefficient arithmetic or executive functioning skills. Methods and Procedures: A DCD and a control group solved word problems with and without scaffolds and conducted a series of tasks measuring calculation and executive skills. Outcomes and Results: Performance improves when scaffolds are presented to children with DCD. Children with DCD and control children differ on executive functioning tasks but perform similarly on arithmetic tests. Conclusions and Implications: Providing scaffolds for word problem solving is effective in children with DCD. Scaffolds possibly reduce the required cognitive load, making the problem solvable for DCD children that have reduced executive functioning skills.